Assessment of isokinetic peak torque reliability of the hip flexor, extensor, adductors and abductors muscles in female soccer players from 14 to 25 years old - Santos Andrade, M.; Mascarin, N. C.; Benedito-Silva, A. A.; Carderelli Minozzo, F.; Vancini R. L.; Barbosa De Lira, C. A. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: